Filming for the future : the work of Louis van Gasteren - Pisters, Patricia (Framing film (Amsterdam, Netherlands), 2016)
Louis Van Gasteren was one of the most prolific filmmakers in the history of the Netherlands, with a resume that includes nearly eighty documentaries and two feature films - to say nothing of artworks and books. Filming for the Future offers an extended exploration of Van Gasteren's work and audio-visual world. Patricia Pisters introduces us to a filmmaker who always had his camera ready and was relentless in filming a wide range of topics and events of national and international importance. Fascinated by technology, deeply engaged with politics, and intensely occupied by the traumatic effects of war, Van Gasteren assembled an unparalleled record of life in twentieth-century Amsterdam and beyond. Filming for the Future will be an invaluable source of documentation and analysis of one of the key filmmakers of our time.